(untitled) (Salam International Academic Journal, 2025)
Human capital is one of the most meaningful and strategic resources in the development equation of nations, playing an increasingly influential role in the process of national growth. Unfortunately, developing and underdeveloped countries, despite their limited income and resources, invest in cultivating such talent in the hope that it will contribute to development. However, due to unfavorable political, economic, social, and security conditions in the country of origin, this talent often chooses to migrate abroad. The purpose of this study is to identify and analyze the push factors contributing to the brain drain from the city of Kunduz, based on Everett Lee’s migration theory. By focusing on adverse economic, social, and security conditions in the country of origin, this research seeks to explain the reasons behind the outmigration of skilled human capital. The study is applied in purpose and descriptive-analytical in methodology, employing statistical tools for analysis. The main research question addresses which factors, in line with Everett Lee’s theory, are most influential in driving the brain drain from Kunduz. The research hypotheses include all origin-based push factors outlined in Everett Lee’s migration theory, along with additional factors identified by the researchers in the field, amounting to a total of seventeen variables. The statistical population includes 155,964 individuals residing in eight districts of Kunduz city. Using the Morgan sampling table, a sample of 382 respondents was selected through proportional stratified sampling. Data were collected using a Likert-scale questionnaire, which was distributed online. The collected data were analyzed using SPSS software, and the reliability of the instrument was confirmed with a Cronbach’s alpha coefficient of 0.865, indicating strong internal consistency. The results of the Friedman ranking test show that among the seventeen hypothesized push factors influencing brain drain from Kunduz, the most significant include economic factors such as unemployment and lack of job opportunities (mean rank 11.39), political instability (11.09), and absence of economic prospects and economic instability (10.93). These are followed by factors such as lack of political stability (9.58), political discrimination (9.56), low salaries and wages (9.52), suppression of political freedoms (9.44), social restrictions (9.20), and lack of personal development opportunities (9.11). Additional influential factors include decline in social welfare (8.38), gender discrimination (8.31), political persecution of elites (8.19), desire for greater political freedom (8.18), physical threats to elites (7.93), social network ties among relatives of elites (5.97), and lack of healthcare and medical facilities (5.92(.